Misconceptions on biodiversity and protist using Three-Tier multiple-choice diagnostic tests - Nurul Amrina Rosada; Herawati Susilo; Abdul Gofur (JURNAL BIOEDUKATIKA, 2022)
Misconceptions are important to know, so that future learning can be improved. This study aims to identify students' misconceptions on the subject of Biodiversity and Protists. This type of research is descriptive quantitative. The sampling technique used in this study was purposive sampling, considering that students who had studied the material on Biological Diversity and Protists had not identified misconceptions and the geographical location of the research site. The research subjects were students of class X SMA Negeri in Kampar Regency, each in two classes, with a total sample of 405 students. The instrument used in the study was a Three-Tier Multiple Choice Diagnostic Test. The study results concluded that the average Percentage of students who had misconceptions about the material on Biodiversity was 32.44% (medium category), and the material Protista was 31.56% (medium category). In the material on Biological Diversity and Protists, many students experience false-negative misconceptions, which means that the information possessed by students is little or incomplete.